Vibrational Raman modes and particle size analysis of cupric oxide with calcination temperature (2019)
In this work a study of the effect of the synthesis conditions on the vibratory and particle size properties in the cupric oxide (CuO) has been presented. The synthesis has been carried out by the polymeric precursor method without modifying the PH in the process, this being a low cost method. The samples obtained have been subjected to several calcination temperatures, 450 °C, 550 °C, 650 °C and 800 °C. In particle analysis by X-ray, scanning electron microscopy (SEM) and statistical it has been observed that for very low or very high calcination temperatures the particle size increases, finding 650 °C as the best calcination temperature. In the Raman spectra, the Ag and Bg vibration have been presented in the samples, with the peaks being narrower for the temperature of 450 °C.